2016
DOI: 10.5271/sjweh.3593
|View full text |Cite
|
Sign up to set email alerts
|

Shift workers have a similar diet quality but higher energy intake than day workers

Abstract: Shift workers have a similar diet quality but higher energy intake than day workers by Hulsegge G, Boer JMA, van der Beek AJ, Verschuren WMM, Sluijs I, Vermeulen R, Proper KI Shift workers, particularly those with five or more night shifts, had a higher energy intake than day workers but similar diet quality. A higher energy intake among shift workers may contribute to shift work-induced adverse health outcomes. If confirmed in future studies, those adverse health outcomes may be alleviated by measures aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 36 publications
2
53
3
4
Order By: Relevance
“…In contrast, a subsequent study adjusting for confounding factors, such as age and BMI, found that shift workers reported a higher energy intake compared to day workers [15]. Although this study did not find any differences in the quality of the diet, several previous studies have suggested that shift work might alter macronutrient distribution and food consumption patterns, such as an increased intake of snacks on night shift.…”
Section: Introductioncontrasting
confidence: 75%
“…In contrast, a subsequent study adjusting for confounding factors, such as age and BMI, found that shift workers reported a higher energy intake compared to day workers [15]. Although this study did not find any differences in the quality of the diet, several previous studies have suggested that shift work might alter macronutrient distribution and food consumption patterns, such as an increased intake of snacks on night shift.…”
Section: Introductioncontrasting
confidence: 75%
“…In a paper by Hulsegge et al (14) in this issue, shift workers were found to have a higher energy intake than day workers (56 kcal/d) and a slightly higher consumption of grains, dairy products, meat and fish and lower consumption of cakes and biscuits. No difference in savory snacks, sweets, soft drinks or juices were found.…”
Section: Does Higher Energy Intake Explain Weight Gain and Increased mentioning
confidence: 93%
“…El consumo de alimentos de los diferentes grupos alimentarios entre hombres y mujeres se presenta en la tabla 3. Otros estudios aplicados a trabajadores de la salud, tampoco lograron encontrar resultados que permitieran asociar modificaciones significativas en la alimentación y el trabajar bajo un sistema por turnos (38,39). En contraposición, un estudio desarrollado en enfermeras en Japón, si demostró una asociación estadísticamente significativa entre las participantes que trabajaron en turnos rotativos y una dieta deficiente (40).…”
Section: Aspectos éTicosunclassified